Precision Assembly Technologies and Systems 5th IFIP WG 5.5 International Precision Assembly Seminar, IPAS 2010, Chamonix, France, February 14-17, 2010. Proceedings - Ratchev, Svetan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 5th International Precision Assembly Seminar, IPAS 2010, in Chamonix, France, in February 2010. The 39 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized in four parts: design of micro products; micro-assembly processes; positioning and manipulation for micro-assembly; and development of micro-assembly production.
Design of Micro Products -- Analysis of the Applicability of Design for Microassembly Theory to Biomedical Devices -- A Haptic Tele-operated System for Microassembly -- Neutral Interface for Assembly and Manufacturing Related Knowledge Exchange in Heterogeneous Design Environment -- Defining Tolerances in Assembly Process with the Aid of Simulation -- Assembly Analysis of Interference Fits in Elastic Materials -- How Form Errors Impact on 2D Precision Assembly with Clearance? -- Micro-assembly Processes -- Precision Assembling and Hybrid Bonding for Micro Fluidic Systems -- Feasibility of Laser Induced Plasma Micro-machining (LIP-MM) -- Focused Ion Beam Micro Machining and Micro Assembly -- Hybrid Assembly for Ultra-Precise Manufacturing -- Development of the Roll Type Incremental Micro Pattern Imprint System for Large Area Pattern Replication -- Utilisation of FIB/SEM Technology in the Assembly of an Innovative Micro-CMM Probe -- Miniaturized Camera Systems for Microfactories -- Vision and Force Sensing to Decrease Assembly Uncertainty -- Modelling the Interaction Forces between an Ideal Measurement Surface and the Stylus Tip of a Novel Vibrating Micro-scale CMM Probe -- Gripping and Feeding Solutions for Micro-assembly -- Alignment Procedures for Micro-optics -- Pneumatic Driven Positioning and Alignment System for the Assembly of Hybrid Microsystems -- Flexure-Based 6-Axis Alignment Module for Automated Laser Assembly -- Approach for the 3D-Alignment in Micro- and Nano-scale Assembly Processes -- Guidelines for Implementing Augmented Reality Procedures in Assisting Assembly Operations -- Monodirectional Positioning Using Dielectric Elastomers -- Active Gripper for Hot Melt Joining of Micro Components -- Grasping and Interaction Force Feedback in Microassembly -- Low Voltage Thermo-mechanically Driven Monolithic Microgripper with Piezoresistive Feedback -- Improvement of Robotic Micromanipulations Using Chemical Functionalisations -- Positioning, Structuring and Controlling with Nanoprecision -- Challenges of Precision Assembly with a Miniaturized Robot -- Development of Micro-assembly Production Systems -- Application of a Reconfiguration Methodology for Multiple Assembly System Reconfigurations -- Multi-agent Architecture for Reconfiguration of Precision Modular Assembly Systems -- Reconfigurable Self-optimising Handling System -- Modular and Generic Control Software System for Scalable Automation -- Agile Multi-parallel Micro Manufacturing Using a Grid of Equiplets -- Development of a Reconfigurable Fixture for the Automated Assembly and Disassembly of High Pressure Rotors for Rolls-Royce Aero Engines -- Architectures and Interfaces for a Micro Factory Concept -- Desktop Micro Forming System for Micro Pattern on the Metal Substrate -- Miniaturization of Flexible Screwing Cell -- A Cooperation Model and Demand-Oriented ICT Infrastructure for SME Development and Production Networks in the Field of Microsystem Technology -- A Methodology for Evaluating the Technological Maturity of Micro and Nano Fabrication Processes -- Function and Length Scale Integration Study in Emerging MST-Based Products.
Keywords: Computer science; Computer simulation; Computer vision; Optical pattern recognition; Engineering; Machinery; Electronics; Computer Science; Simulation and Modeling; Nanotechnology and Microengineering; Manufacturing, Machines, Tools; Electronics and Microelectronics, Instrumentation; Pattern Recognition; Image Processing and Computer Vision